Etomidate and Ketamine: Residual Motor and Adrenal Dysfunction that Persist beyond Recovery from Loss of Righting Reflex in Rats - Daniel Diaz-Gil; Noomi Mueller; Ingrid Moreno-Duarte; Hsin Lin; Cenk Ayata; Cristina Cusin; Joseph F. Cotten; Matthias Eikermann (MDPI AG, 2014)
We tested the hypothesis that etomidate and ketamine produce residual effects that modify functional mobility (measured by the balance beam test) and adrenal function (adrenocorticotropic hormone (ACTH) stimulation) immediately following recovery from loss of righting reflex in rats. Intravenous etomidate or ketamine was administered in a randomized, crossover fashion (2 or 4 mg/kg and 20 or 40 mg/kg, respectively) on eight consecutive days. Following recovery of righting reflex, animals were assessed for residual effects on functional mobility on the balance beam, motor behavior in the open field and adrenal function through ACTH stimulation. We evaluated the consequences of the effects of the anesthetic agent-induced motor behavior on functional mobility. On the balance beam, etomidate-treated rats maintained their grip longer than ketamine-treated rats, indicating greater balance abilities (mean ± SD, 21.5 ± 25.1 s vs. 3.0 ± 4.3 s respectively, p < 0.021). In the open field test, both dosages of etomidate and ketamine had opposite effects on travel behavior, showing ketamine-induced hyperlocomotion and etomidate-induced hypolocomotion. There was a significant interaction between anesthetic agent and motor behavior effects for functional mobility effects (p < 0.001). Corticosterone levels were lower after both 40 mg/kg ketamine and 4 mg/kg etomidate anesthesia compared to placebo, an effect stronger with etomidate than ketamine (p < 0.001). Following recovery from anesthesia, etomidate and ketamine have substantial side effects. Ketamine-induced hyperlocomotion with 20 and 40 mg/kg has stronger effects on functional mobility than etomidate-induced hypolocomotion with 2 and 4 mg/kg. Etomidate (4 mg/kg) has stronger adrenal suppression effects than ketamine (40 mg/kg).